ANALISA BEBAN STATIS STRUKTUR KOMPOSIT BERDASARKAN ORIENTASI ARAH SERAT PADA KOMPONEN FAIRING FLAP ARMS PESAWAT NC-212 MENGGUNAKAN SOFTWARE ANSYS - Muhamad Rizki Ardiansyah; Dedi Suryadi; Hendri Hestiawan (UNIB Press, 2026)
The advancement of composite material technology has significantly contributed to enhancing aircraft structural performance, komponen icularly in terms of weight efficiency and mechanical resistance. This study aims to analyze the influence of fiber orientation on the static response of a composite structure applied to the fairing flap arms component of the NC-212 aircraft. The analysis was conducted through simulation using ANSYS Workbench 2025 based on the Finite Element Method (FEM). The material used is glass fiber fabric/epoxy resin type 181 with various fiber orientation configurations, including (0°, 0°, 0°, 0°), (90°, 90°, 90°, 90°), (45°, -45°, 45°, -45°), (0°, -45°, 45°, 0°), (0°, 90°, 90°, 0°), and (90°, -45°, 45°, 90°). The results indicate that the fiber orientation of (45°, -45°, 45°, -45°) produces the highest Total deformasiof 0.091405 mm and the highest Von Mises stress of 89.132 MPa, along with the highest safety factor of 4.4791. Conversely, the (0°, -45°, 45°, 0°) orientation shows the lowest deformation at 0.07997 mm. These findings emphasize that fiber orientation significantly affects the mechanical behavior of composite structures. Diagonal fiber configurations tend to result in higher deformation and stress levels compared to unidirectional or perpendicular orientations.